40.0k views
21 votes
Whats the soulution to the stimultaneous equation 2x-3y=-1 and y=2x+3

User Vilis
by
7.7k points

1 Answer

8 votes
Answer: x = -2, y = -1

Explanation:

Lets solve this by Substitution;

=> 2x - 3y = -1 (Eq. 1)
=> y = 2x + 3 (Eq. 2)

From Eq. 2 we get the value of ‘y’ in terms of ‘x’

Substitute value of ‘y’ from Eq. 2 in 1 :-

2x - 3y = -1
2x - 3(2x + 3) = -1
2x - 6x - 9 = -1
-4x - 9 = -1
-4x = -1 + 9 = 8
=> x = 8/-4 = -2

Therefore, x = -2

Substitute value of ‘x’ in Eq. 2 :-

y = 2x + 3
y = 2(-2) + 3
=> y = -4 + 3 = -1

Therefore, y = -1
User Usman Shaukat
by
8.3k points

Related questions

asked Sep 2, 2024 9.6k views
Vitor Vicente asked Sep 2, 2024
by Vitor Vicente
7.5k points
1 answer
5 votes
9.6k views
asked Mar 7, 2022 234k views
PaulDapolito asked Mar 7, 2022
by PaulDapolito
7.9k points
1 answer
2 votes
234k views